Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/peps.12050
|View full text |Cite
|
Sign up to set email alerts
|

When Do Employees Speak up for Their Customers? A Model of Voice in a Customer Service Context

Abstract: We develop a conceptual model of customer‐focused voice and test it in a hospital setting. Drawing from theory and research on voice, we find that customer orientation and job autonomy are positively associated with customer‐focused voice. In addition, consistent with social information processing theory, these relationships are moderated by service climate, such that a high service climate compensates for the less desirable aspects of employees or their jobs. Finally, we provide evidence for a critical but un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 94 publications
3
123
1
1
Order By: Relevance
“…Based on this evidence, Morrison suggested that felt responsibility , job satisfaction , social support , and work‐group and organizational identification would motivate voice, and psychological detachment would inhibit voice. In addition, voice is likely when individuals have personal authority over their work and can endorse their actions (Lam & Mayer, ; Liu et al., ), feel a psychological bond to the organization (Burris et al., ; Farh, Hackett, & Liang, ), and perceive the organization to be fair (Zhang, LePine, Buckman, & Wei, ). Based on these arguments, we suggest that autonomy , organizational commitment , and organizational justice will be positively related to voice.…”
Section: An Integrative Examination Of Voice and Its Promotive And Prmentioning
confidence: 99%
“…Based on this evidence, Morrison suggested that felt responsibility , job satisfaction , social support , and work‐group and organizational identification would motivate voice, and psychological detachment would inhibit voice. In addition, voice is likely when individuals have personal authority over their work and can endorse their actions (Lam & Mayer, ; Liu et al., ), feel a psychological bond to the organization (Burris et al., ; Farh, Hackett, & Liang, ), and perceive the organization to be fair (Zhang, LePine, Buckman, & Wei, ). Based on these arguments, we suggest that autonomy , organizational commitment , and organizational justice will be positively related to voice.…”
Section: An Integrative Examination Of Voice and Its Promotive And Prmentioning
confidence: 99%
“…In order for employees to engage in proactive behaviors, they must perceive that there are reasons to engage in these behaviors (Morrison & Phelps, ; Parker, Wall, & Jackson, ; Tangirala & Ramanujam, ). Research has shown that those who are dedicated to benefit the recipients of proactive behaviors (e.g., peers, customers, work units, or organization) are more likely to engage in proactive behaviors (Lam & Mayer, ; Tangirala & Ramanujam, ). Thus, the importance of these two motivational pathways is well‐established (Parker & Wu, ).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…For example, employees with higher proactive personality are more likely to be promoted (Seibert, Kraimer, & Crant, ), and those who proactively seek information and build relationships with superiors are more likely to perform better and be more satisfied at work (Ashford & Black, ). In terms of organizational outcomes, proactive individuals who speak up to benefit their customers are perceived to offer better service (Lam & Mayer, ), and proactive planning by business owners is associated with greater business size and objective evaluation of business success (Frese et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…When employees voice, they draw on their experience and proximity to work operations, and thus communicate valuable information in the form of actionable suggestions based on their uniquely held viewpoints and knowledge (Edmondson, 1996). Voice can thus help organizations avoid errors (Edmondson, 2003), enhance innovation (Liu et al, 2017), and increase performance as indexed by sales, profits, and customer satisfaction (Detert, Burris, Harrison, & Martin, 2013;Frazier & Bowler, 2015;Lam & Mayer, 2014;MacKenzie, Podsakoff, & Podsakoff, 2011). Crucially, for voice to have such an impact, it needs to be endorsed Dutton & Ashford, 1993) because employees often lack the influence needed to turn their ideas or opinions into real constructive changes (Morrison, 2014;Tangirala & Ramanujam, 2012).…”
Section: Introductionmentioning
confidence: 99%